EXPANDING THE CONCEPT OF HEALTH EDUCATION AND STIMULATING PRACTICE IN GRADUATION BY CRITICAL-REFLEXIVE METHODOLOGY: EXPERIENCE REPORT - Regina, Marcia [UNESP]; Rocha, Alves [UNESP]; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education A& Development, 2016)
The transmission of knowledge still dominates the educational practices. How to contribute to change this scenario? This report aims to extend the concept of health education of students and encourage the use of alternative methods in the community. This story occurred with 28 undergraduate students of health courses: nursing, dentistry, physiotherapy, nutrition and biology through the Health Education course at a private institution. In class students elaborated interdisciplinary projects to perform in the community supported the concept that health education is not limited just to inform or change behavior but to prepare individuals for the exercise of full citizenship, so that they become able to fulfill your order duties to obtain the common good and better quality of life for all and especially enable these actors become capable of transforming society as subjects of their own history. The difference is that the activities were planned from the community's needs and the results were discussed and presented in the classroom. Teacher uses constructivism in the classroom (questioning). In the construction of the projects the students realize that they are proposing transmissive educational practices without considering the community's previous ideas. The concept of health education is emerging texts and group discussions. The teacher is supported by Vygotsky to the construction of knowledge. The understanding and broadening of the concept of Health Education will occur along the experiences and build together the projects that translate into booklets, games, meeting groups in the community. Discipline is recognized by 92% of the differential of its course, as it enables better understanding of the community and build relationships. The practice in the community helps to reflect on the importance of dialogue built without authoritarianism and imposition of truths. Supported on the understanding that no one teaches anyone and that learning is mediated world, the university has a key role in this process.